Peningkatan Produksi Plastik Injection dengan Analisis Overall Equipment Effectiveness dan Single Minute Exchange of Dies - Supriyati Supriyati; Tri Ngudi Wiyatno; Heru Darmawan (Universitas Mercu Buana, 2021)
The automotive industry is a mainstay because it has a contribution to the national economy. To maintain existence and survive in the midst of intense competition, every industry must be able to continuously improve the quality and performance company in general. Plastic injection manufacturing companies for automotive components are experiencing a decline in machine performance. Machine performance is related to losses that occur in the company. To find out the cause of a decline in machine performance, research is carried out by identifying processes, outputs, losses that occur and taking other actions if needed. Results of OEE calculation analysis, machine 7 has the lowest performance of a total of 8 machines. Low OEE value is influenced by availability, performance, and quality, of three components, the lowest average availability value is only 90%, machine 7 OEE is 81%. Factors affecting OEE are low because the value of availability is low. After analyzing with fishbone diagram, the cause of low availability is due to machine and method factors. Improvement to machine 7 using the SMED method showed a decrease in setup time by 36%, while improvements were made by changing setup flow, replacing machine components, and purging process. Impact of improvements increased availability by 96%, performance, and quality by 99%, while machine efficiency/OEE increased by 93,98%.